1994
DOI: 10.1073/pnas.91.6.2046
|View full text |Cite
|
Sign up to set email alerts
|

Inducible isoforms of cyclooxygenase and nitric-oxide synthase in inflammation.

Abstract: Cyclooxygeuase (COX) progressively, also peakingatday 14. COX-1 protein remained unaltered throughout. The iNOS activity increased over the first 24 h in the skin, with a further major increase in the granulomatous tissue between days 3 and 7, followed by a decrease at day 14 and a further increase at day 21. The rise in COX and NOS activities in the skin during the acute phase reinforces the proinflammatory role for prostanoids and suggests one also for nitric oxide. However, in the chronic and resolving st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
518
3
11

Year Published

1996
1996
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 965 publications
(543 citation statements)
references
References 48 publications
11
518
3
11
Order By: Relevance
“…As part of the NTP assessment, the Centers for Disease Control and Prevention (CDC) measured methyl eugenol exposure in a non-representative sample of adults in the U.S. as part of the Third National Health and Nutrition Examination Survey (NHANES III, 1988-1994. According to Robison and Barr (19), methyl eugenol has a relatively short half-life so exposure assessment needs to include data related to when food was consumed relative to the collection of blood samples.…”
Section: Consumption and Exposure Assessment Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…As part of the NTP assessment, the Centers for Disease Control and Prevention (CDC) measured methyl eugenol exposure in a non-representative sample of adults in the U.S. as part of the Third National Health and Nutrition Examination Survey (NHANES III, 1988-1994. According to Robison and Barr (19), methyl eugenol has a relatively short half-life so exposure assessment needs to include data related to when food was consumed relative to the collection of blood samples.…”
Section: Consumption and Exposure Assessment Challengesmentioning
confidence: 99%
“…Cyclooxygenase (COX) has a critical role in the inflammatory process and has been shown to contribute to pain, swelling, and stiffness (66,67). Likewise, the LOX pathway produces leukotrienes which, like PGs, are potent causal pain agents.…”
Section: Inflammation-sincementioning
confidence: 99%
“…16,27,33 There is extensive evidence based on animal, as well as human studies supporting the role of COX-2 in the development of inflammation. 27,32,34 Animal models of inflammation have demonstrated that COX-2 mRNA and protein as well as PGs increase in a time-dependent manner that parallels the inflammatory process. 1 Inflammatory cytokines and endotoxins can induce a 10 to 80-fold increase in the level of COX-2 expression in monocytes, macrophages, chondrocytes, fibroblasts, and endothelial cells.…”
Section: Introductionmentioning
confidence: 99%
“…NO has been reported to modulate the activity of COX-2 in a cGMP-independent manner, and NO plays a critical role in the release of PGE 2 by direct activation of COX-2 (Salvemini et al, 1993). NO production has been shown as a key regulator of homeostasis and NO is known as an important mediator of inflammation in several animal models (Vane et al, 1994). Especially, the generation of NO by iNOS plays an important role in inflammation, host-defense responses, and tissue repair (Nathan and Xie, 1994).…”
Section: Discussionmentioning
confidence: 99%